(untitled) (Revista Contexto & Saúde, 2024)
This study aims to describe the lipid profile of children and adolescents living in the quilombola communities of Médio Itacuruçá (Abaetetuba) and Santo Antônio (Concórdia do Pará) in the state of Pará. This observational, descriptive cross-sectional study is based on a secondary database from the project "Epidemiological, clinical and toxicological characterization in two communities environmentally exposed to pesticides in Pará state." The chi-square test and Student’s t-test were used to analyze the following variables: weight, height, body mass index, total cholesterol, low-density lipoprotein (LDL), low-density lipoprotein (HDL), and triglycerides in males and females aged 2 to 9 years and 10 to 19 years. The 10-19 age group accounted for 68.7% of the study population. Hypercholesterolemia was identified in 36.4% of the patients, altered LDL in 15.2%, and HDL below the reference value in 60.6%. As for triglycerides, 90.3% of patients aged 2 to 9 years had altered values, and 63.2% of patients aged 10 to 19 years had hypertriglyceridemia. Around 64.6% of the patients had an eutrophic nutritional profile. It was concluded that most children and adolescents had total cholesterol and LDL values within the normal range. However, significant results were obtained for HDL cholesterol and triglycerides above the reference values.